Large-scale investigation on healthy status of teachers in Jiangsu Province, China - Zheng, Chunlin; Shi, Cheng; Bai, Jianling; Shao, Wentao; Zhang, Chunlan; Bu, Jin (Progress in Nutrition, 2019)
Objective: We conducted this cross section study to investigate the basic health status of teachers in Jiangsu. Design: Healthy data of teachers from Chinese Teacher Cohort were collected by an online questionnaire and scored by a diet behavior system with maximum score of 28. Setting: The health of teachers is not only a sociopolitical topic, but also an interdisciplinary challenge, while few researches focused on the basic healthy information of above teacher population. Subjects: A total of 22,956 teachers aged 20-65 year registering in Jiangsu Province Education System completed the questionnaire survey. Results: The average Dietary habits score of participants was 14.0±3.0 based on a full score of 28, which is the worst. The Dietary habits score increased with age (P